2007
DOI: 10.1111/j.1600-0625.2006.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of down‐regulated acetaldehyde dehydrogenase 1 in atopic dermatitis patients by two‐dimensional electrophoresis

Abstract: We conducted the proteomic studies to detect the dysregulated proteins in the atopic dermatitis (AD) proteome obtained from the patient-derived primary cultured fibroblasts. Acetaldehyde dehydrogenase 1 (ALDH1) was detected as being significantly down-regulated at the pH ranges of 6-9 and 4-7. The transcriptional levels of ALDH1, as detected by RT-PCR and real-time PCR, further confirmed the down-regulated phenomena for all the AD-fibroblasts (n = 20). The expression levels of ALDH1 in the whole skin tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
(27 reference statements)
0
8
0
1
Order By: Relevance
“…The expression of the major RA synthesizing enzyme in the skin the RALDH1 is significantly decreased in AD skin versus healthy skin (25). This strong down‐regulation in affected and non‐affected AD skin is suggested to be mainly responsible for lower ATRA concentrations and thereby for the significantly lower retinoid‐mediated signalling in the skin of patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the major RA synthesizing enzyme in the skin the RALDH1 is significantly decreased in AD skin versus healthy skin (25). This strong down‐regulation in affected and non‐affected AD skin is suggested to be mainly responsible for lower ATRA concentrations and thereby for the significantly lower retinoid‐mediated signalling in the skin of patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ayu bacteremia (also known as blood poisoning or toxemia) caused by Aeromonas hydrophila, has been posing a serious threat to cultured ayu in China, but cellular and molecular processes involved in disease response are poorly understood. To explore it, we have analyzed the liver proteins by using two-dimensional gel electrophoresis (2DE) in combination with mass spectrometry (MS) [10]. The results showed that the increased ayu liver NKEF-B mRNA and protein expression were closely associated with A. hydrophila infection.…”
mentioning
confidence: 97%
“…In further works, Park et al carried out a cDNA microarray analysis of fibroblasts from ADe and ADi where they suggested that human dermal fibroblasts may actively participate in AD disease [57] and proposed acetaldehyde dehydrogenase 1 (ALDH1) as a biomarker for AD disease using proteomic profiling of fibroblasts from ADi and ADe samples [58]. …”
Section: Atopic Dermatitismentioning
confidence: 99%